Pertimbangan Penyidik dalam Menerapkan Diskresi terhadap Anak yang Berkonflik dengan Hukum dalam Perspektif Prinsip Kepentingan Terbaik bagi Anak - Nanda Henriusta; Nizar Fahmi; Ahmad Wisnu Syaifuddin; Agha Prambudi (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2026)
This study aims to analyze investigators’ considerations in exercising discretion toward children in conflict with the law from the perspective of the best interests of the child principle. Discretion, as an inherent authority of investigators, often results in varied implementation practices, potentially affecting the protection of children's rights within the criminal justice process. This research employs normative legal research methods with statutory and conceptual approaches. Legal materials are analyzed qualitatively through systematic interpretation of relevant provisions within the Criminal Procedure Code, the Juvenile Criminal Justice System Act, and the best interests of the child principle as part of the child rights protection regime. The findings indicate that investigators’ discretion must be grounded in objective parameters, including the child’s level of culpability, the impact of the offense, the interests of the victim, and guarantees of rehabilitation and social reintegration. Discretion that is not aligned with the best interests of the child principle may lead to disparity and undermine restorative justice objectives. Therefore, structured and measurable standards are necessary to ensure that discretionary decisions genuinely reflect child protection and substantive justice within the juvenile criminal justice system.